2015
DOI: 10.1038/ncomms7095
|View full text |Cite
|
Sign up to set email alerts
|

The jasmonate-responsive GTR1 transporter is required for gibberellin-mediated stamen development in Arabidopsis

Abstract: Plant hormones are transported across cell membranes during various physiological events. Recent identification of abscisic acid and strigolactone transporters suggests that transport of various plant hormones across membranes does not occur by simple diffusion but requires transporter proteins that are strictly regulated during development. Here, we report that a major glucosinolate transporter, GTR1/NPF2.10, is multifunctional and may be involved in hormone transport in Arabidopsis thaliana … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
153
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(155 citation statements)
references
References 52 publications
2
153
0
Order By: Relevance
“…Some members already identified in plants are H + /substrate symporters that utilize the inwardly direct proton gradient (Dm H + ) across the cell membrane and drive the uptake of the substrates (Krouk et al, 2010;Nour-Eldin et al, 2012;Léran et al, 2014;Saito et al, 2015;Tal et al, 2016). However, this study reveals that NRT1.5 functions as a protoncoupled H + /K + antiporter, and external acidic pH promotes K + release out of cells (Figures 7 and 8).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Some members already identified in plants are H + /substrate symporters that utilize the inwardly direct proton gradient (Dm H + ) across the cell membrane and drive the uptake of the substrates (Krouk et al, 2010;Nour-Eldin et al, 2012;Léran et al, 2014;Saito et al, 2015;Tal et al, 2016). However, this study reveals that NRT1.5 functions as a protoncoupled H + /K + antiporter, and external acidic pH promotes K + release out of cells (Figures 7 and 8).…”
Section: Discussionmentioning
confidence: 51%
“…Arabidopsis and rice (Oryza sativa) contain 53 and 80 NRT1/PTR members, respectively (Tsay et al, 2007), which implies that these proteins have diverse functions in plants, not necessarily limited to nitrate and peptide transport. Most of the identified members in plants are nitrate transporters, but some transport different substrates, for example, indole-3-acetic acid, abscisic acid, gibberellic acid, jasmonoyl-isoleucine, glucosinolates, or amino acids (Krouk et al, 2010;Nour-Eldin et al, 2012;Léran et al, 2014;Saito et al, 2015;Tal et al, 2016). In this study, we identified K + as a novel substrate of NRT1/PTR transporters.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recent studies suggest that GA movement and distribution might be regulated by a group of GA transporters (Chiba et al, 2015;Saito et al, 2015). The NITRATE TRANSPORTER 1/PEPTIDE TRANSPORTER FAMILY (NPF) is a family of proteins initially identified as nitrate or peptide transporters (Tsay et al, 2007;Léran et al, 2014), and was later found to also transport hormones such as auxin and abcisic acid (Krouk et al, 2010;Kanno et al, 2012).…”
Section: Tem Affects Palisade Mesophyll Development and Ga Transportmentioning
confidence: 99%
“…9 Recently, biochemical studies in heterologous systems allowed the identification of several GA transporters, belonging to the NITRATE TRANSPORTER 1/PEPTIDE TRANSPORTER FAMILY (NPF). [15][16][17] The NPFs represent a large family of membrane proteins which transport a wide array of compounds including nitrate, peptides, glucosinolates and phytohormones. 18 Although not demonstrated, it is tempting to speculate that these multifunctional transporters may contribute in the translocation of GA 12 from parenchyma cells to the vessels.…”
Section: Article Addendummentioning
confidence: 99%